Factors Influencing Intention to Use Online Job Portals among Pokhara University Graduates - Ranabhat, Deepesh; Poudel, Shristi; Khanal, Richa; Tripathee, Sudip; Ranabhat, Mala (Journal of Development and Social Engineering, 2025)
Online job portals have gained popularity among both employers and job applicants. This paper investigates the factors influencing intention to use online job portals among fresh graduates. A convenience sampling technique was administered among 255 BBA and MBA graduates of Pokhara University. A close-ended structured questionnaire was administered both physically and using Google Forms. This study used both descriptive as well as inferential statistical tools, including mean score analysis, correlation analysis, and regression analysis. The study found that perceived ease of use, usefulness, and hedonic value have statistically significant impact on graduates’ attitudes toward using online job portals, which, in turn, affects intention to use. However, perceived privacy and security found insignificant. This study concludes that organizations that focus on user-friendly job sites, offer valuable features, and enhance the overall user experience can attract top talent through online job portals. The findings support the global trend of digitalization in recruitment processes. Nepalese organizations may benefit from adopting e-recruitment practices, as fresh graduates show positive attitudes and intentions toward online job portals.